The aflatoxin B(1) formamidopyrimidine adduct plays a major role in causing the types of mutations observed in human hepatocellular carcinoma - Smela, Maryann E. (The National Academy of Sciences, 2002)
A G to T mutation has been observed at the third position of codon 249 of the p53 tumor-suppressor gene in over 50% of the hepatocellular carcinoma cases associated with high exposure to aflatoxin B(1) (AFB(1)). Hypotheses have been put forth that AFB(1), in concert with hepatitis B virus (HBV), may play a role in the formation of, and/or the selection for, this mutation. The primary DNA adduct of AFB(1) is 8,9-dihydro-8-(N(7)-guanyl)-9-hydroxyaflatoxin B(1) (AFB(1)-N7-Gua), which is converted naturally to two secondary lesions, an apurinic site and an AFB(1)-formamidopyrimidine (AFB(1)-FAPY) adduct. AFB(1)-FAPY is detected at near maximal levels in rat DNA days to weeks after AFB(1) exposure, underscoring its high persistence in vivo. The present study reveals two striking properties of this DNA adduct: (i) AFB(1)-FAPY was found to cause a G to T mutation frequency in Escherichia coli approximately 6 times higher than that of AFB(1)-N7-Gua, and (ii) one proposed rotamer of AFB(1)-FAPY is a block to replication, even when the efficient bypass polymerase MucAB is used by the cell. Taken together, these characteristics make the FAPY adduct the prime candidate for both the genotoxicity of aflatoxin, because mammalian cells also have similar bypass mechanisms for combating DNA damage, and the mutagenicity that ultimately may lead to liver cancer.